Salvage Repair of Vesicovaginal Fistula - Yarmohamadi, Aliasghar; Asl Zare, Mohammad; Ahmadnia, Hassan; Mogharabian, Nasser (Urology Journal, 2011)
Purpose: To present the long-term results of failed vesicovaginal fistula repair using flap splitting techniques. Materials and Methods: Nine women with a previous failed vesicovaginal fistula repair, aged 18 to 69 years, underwent salvage vaginal reconstruction for damaged urethra or bladder, at a five-year interval lasting from 2003 to 2007. Fistulas were repaired using an interposed pediculated vaginal wall flap. Results: The repair was successful in all the patients, even in those with rectovesicovaginal fistula or a large vesicovaginal fistula with sphincter damage. Conclusion: Pediculated vaginal wall flap is an easily-prepared, well-vascularized tissue, which provides long-term favorable outcomes.